The electro-mechanical tensile properties of an engineered cementitious composite. Issue 11 (24th November 2021) - Saraireh, Danah; Suryanto, Benny; McCarter, William John; Walls, Steven
Abstract : The influence of ongoing cement hydration and multiple microcrack formation on the electrical impedance of an engineered cementitious composite (ECC) is presented. Impedance measurements were obtained over the frequency range 20 Hz–1 MHz and displayed in the Nyquist format. In addition, the permittivity and conductivity were de-embedded from the measured impedance and presented in both time and frequency domains to elucidate the nature of conduction and polarisation processes. It was found that, over a curing period of 90 days, the ECC displayed a classic impedance response. Both conductivity and relative permittivity were found to be frequency dependent due to bulk relaxation processes operating within the composite. Tensile straining was shown to result in a detectable change in the impedance response, but retained a similar overall profile. When presented in the frequency domain, a downward displacement in both conductivity and relative permittivity profiles was evident with increasing tensile strain. It is shown that the relative permittivity at the high-frequency end could be exploited as a potentially useful indicator for strain/damage detection. The influence of microcracking on the piezo-resistive response of the composite is discussed based on crack patterns obtained from both visual observations and digital image correlation.